The use of piezocone tests for high-resolution stratigraphy of Quaternary Sediment Sequences in the Brazilian coast - De Mio, Giuliano; Giacheti, Heraldo L. (FapUNIFESP (SciELO), 2007)
Correlations between mapping units of costal sedimentary basin and interpretation of piezocone test results are presented and discussed based on examples from Caravelas strandplain, (State of Bahia), Paranaguá (State of Paraná) and Guarujá bays (State of São Paulo), Brazil. Recognizing that the sedimentary environment was mainly controlled by sea level fluctuations led to the interpretation of transgressive and regressive sedimentary sequences, which is in a good agreement with the sea level fluctuation curves currently accepted for these regions. The interpretation of piezocone test results shows that the sedimentary sequences of Caravelas and Guarujá sites are similar and they have a good correlation to the sea level fluctuation curve accepted for Salvador region, State of Bahia. On the other hand, the piezocone test results from Paranaguá site indicate a different sedimentary sequence from the previous ones, relating to the sea level fluctuation curve accepted for Paranaguá region. The results show the high applicability of piezocone testing for stratigraphical logging and suggest that it is possible to integrate it with other current techniques used for paleo-environmental studies in Brazil, in accordance with recent approaches used in international research on the subject.
Keywords: Geological mapping; Paleoenvironment; Piezocone test; Stratigraphic logging